After access - Challenges facing mobile-only internet users in the developing world - Gitau, Shikoh; Marsden, Gary; Donner, Jonathan (Proceedings of the 28th international conference on human factors in computing systems (CHI 2010), 2010)
This study reports results of an ethnographic action research study, exploring mobile-centric internet use. Over the course of 13 weeks, eight women, each a member of a livelihoods collective in urban Cape Town, South Africa, received training to make use of the data (internet) features on the phones they already owned. None of the women had previous exposure to PCs or the internet. Activities focused on social networking, entertainment, information search, and, in particular, job searches. Results of the exercise reveal both the promise of, and barriers to, mobile internet use by a potentially large community of first-time, mobile centric users. Discussion focuses on the importance of self expression and identity management in the refinement of online and offline presences, and considers these forces relative to issues of gender and socioeconomic status.